Role of Serum Levels of Angiogenic Cytokines in Assessment of Angiogenesis after Stem Cell Therapy of Diabetic Patients with Critical Limb Ischemia. Issue 12 (December 2014) - Dubsky, Michal; Jirkovska, Alexandra; Bem, Robert; Fejfarova, Vladimira; Varga, Martin; Kolesar, Libor; Pagacova, Libuse; Sykova, Eva; Jude, Edward. B.
The release of proangiogenic cytokines into the circulation after stem cell (SC) therapy and compensatory increase of angiogenesis inhibitors may reflect local vasculogenesis but also can increase the risk of side effects. The aim of our study was to evaluate serum levels of angiogenic cytokines with regard to the assessment of local and systemic vasculogenesis in diabetic patients with no-option critical limb ischemia (NO-CLI). Twenty-five diabetic patients with NO-CLI treated with SCs isolated from bone marrow or stimulated peripheral blood were included in the study. Serum levels of proangiogenic cytokines (VEGF, bFGF, Ang-1, PDGF-AA, and PDGF-BB) and an antiangiogenic cytokine (endostatin) were assessed 6 months after cell treatment, compared to baseline values, and correlated with the number of injected CD34 + cells. The clinical effect of SC therapy (assessed by changes in TcPO2 ) and potential systemic vasculogenesis (assessed by eye fundus examination) were evaluated after 6 months. Serum levels of angiogenic inhibitor endostatin increased significantly after 1 and 3 months ( p = 0.0003), but no significant increase in serum levels of proangiogenic cytokines was observed. A significant correlation between number of injected CD34 + cells and serum levels of endostatin was observed ( r = 0.41, p < 0.05); however, proangiogenic cytokines did not correlate with CD34 + cells. No correlation between increase in TcPO2 after treatment and serum levels of any of the angiogenic cytokines were seen, and no signs of systemic vasculogenesis in the retina were observed after 6 months. Despite the significant increase in the levels of the angiogenic inhibitor endostatin following SC treatment, there was no risk of systemic vasculogenesis after SC therapy as documented by serum levels of proangiogenic cytokines or changes in the retina.